Altered Gut Microbiome in Patients With Dermatomyositis. Issue 8 (26th May 2022) - Bae, Sangmee Sharon; Dong, Tien S.; Wang, Jennifer; Lagishetty, Venu; Katzka, William; Jacobs, Jonathan P.; Charles‐Schoeman, Christina
Abstract : Objective: The study objective was to compare the microbial composition of patients with dermatomyositis (DM) and healthy controls (HCs) and determine whether microbial alterations are associated with clinical manifestations of DM. Methods: The 16S ribosomal RNA gene sequencing was performed on fecal samples from patients with DM and HCs. Microbial composition and diversity were compared between subjects with DM and HCs and in association with several DM‐specific clinical variables, including myositis‐specific autoantibodies (MSAs). Differentially abundant microbial taxa and genes associated with clinical characteristics were identified, and functional analysis was performed using predicted metagenomics. Dietary intake was assessed using a 24‐hour dietary recall. Results: The fecal microbiome of 36 patients with DM and 26 HCs were analyzed. Patients with DM trended toward lower microbial diversity compared with HCs. The higher physician global damage score was significantly correlated with the lower microbial diversity in patients with DM. Patients with interstitial lung disease (ILD)‐associated MSA (antisynthetase antibody (ab), anti‐melanoma differentiation‐associated protein 5 ab, n = 12) had significant differences in microbial composition and lower microbial diversity compared with HCs. Differential abundance testing demonstrated a unique taxonomic signature in the ILD‐MSA subgroup, and predictive metagenomics identified functional alterations in a number of metabolic pathways. A significant increase in the relative abundance of Proteobacteria was positively correlated with multiple pathways involved in lipopolysaccharide synthesis and transport in the ILD‐MSA group. Conclusion: Patients with DM, particularly with ILD‐associated MSAs, have lower microbial diversity and a distinct taxonomic composition compared with HCs. Further studies are needed to validate our findings and elucidate specific pathogenetic mechanisms that link the gut microbiome to clinical and pathological features of DM.